World Economic Outlook, April 2016 : Too Slow for Too Long. (World Economic Outlook; World Economic Outlook ;, 2016)
Major macroeconomic realignments are affecting prospects differentially across the world's countries and regions. The April 2016 WEO examines the causes and implications of these realignments-including the slowdown and rebalancing in China, a further decline in commodity prices, a related slowdown in investment and trade, and declining capital flows to emerging market and developing economies-which are generating substantial uncertainty and affecting the outlook for the global economy. Additionally, analytical chapters examine the slowdown in capital flows to emerging market economies since their 2010 peak-its main characteristics, how it compares with past slowdowns, the factors that are driving it, and whether exchange rate flexibility has changed the dynamics of the capital inflow cycle-and assess whether product and labor market reforms can improve the economic outlook in advanced economies, looking at the recent evolution and scope for further reform, the channels through which reforms affect economic activity under strong versus weak economic conditions, reforms' short- to medium-term macroeconomic effects, and sequencing of reforms and coordination with other policies to maximize their potential quantitative economic benefits. A special feature analyzes in depth the energy transition in an era of low fossil fuel prices.